2010
DOI: 10.1007/s12032-010-9525-0
|View full text |Cite
|
Sign up to set email alerts
|

Importance of ATM gene as a susceptible trait: predisposition role of D1853N polymorphism in breast cancer

Abstract: The involvement of ATM gene and specifically, the important role of D1853N polymorphism, as a three-hit hypothesis has been previously reported in an Iranian proband affected with brain tumor and this polymorphism could be screened in her relatives as well. The aim of present study was to investigate the involvement of D1853N polymorphism as a predisposition factor in 129 Iranian patients affected with primary breast cancer and 248 sex- and age-matched healthy controls. Mutant allele-specific PCR amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Similar results were found by Mehdipour and colleagues 14 in Iranian population, in which the authors found a heterozygote frequency of 31% in cases vs. 18.6% in controls. These results differ significantly from those obtained in this study, probably because they are populations with different genetic background.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were found by Mehdipour and colleagues 14 in Iranian population, in which the authors found a heterozygote frequency of 31% in cases vs. 18.6% in controls. These results differ significantly from those obtained in this study, probably because they are populations with different genetic background.…”
Section: Discussionsupporting
confidence: 89%
“…The polymorphism 5557G>A (D1853N), located in exon 39 of the ATM gene, has been studied by Mehdipour and colleagues, 14 who proposed it as a predisposing factor for developing BC, especially in familial cases. The study was conducted in an Iranian population of women with BC and in a healthy control group divided into two subgroups, one randomly selected and the other with a family history, reporting a carrier frequency of 31% in the disease group and 18.6% in controls.…”
Section: Studies Of Polymorphism 5557g>amentioning
confidence: 99%
“…Of these studies, the sample sizes ranged from 184 [13] to 2,884 [11] individuals. One study deviated from the HWE at a significance level of P = 0.01 in controls [11] and another two studies by Mehdipour et al [18] and Koren et al [13] had no available data for HWE. The genotypes and separate P values for ATM 5557G[A, IVS38-8T[C, IVS1?19A[T, and IVS34?60G[A polymorphisms included in the meta-analysis are shown in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 94%
“…Following the above inclusion and exclusion criteria, nine publications were included in this meta-analysis [4,[11][12][13][14][15][16][17][18]. Some case-control studies presented the ORs separately for more than one kind of ATM polymorphism [4,11,15,16].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, as the study by Tapia et al [3] was not in Hardy-Weinberg equilibrium (HWE) in controls, it should be excluded in the final meta-analysis. In addition, the meta-analysis by Gao L et al [2] omitted one eligible study [8] and included one ineligible study [3]. Therefore, we re-assessed the association between ATM 5557G[A polymorphism and breast cancer (Fig.…”
mentioning
confidence: 99%